2019
DOI: 10.1073/pnas.1813254116
|View full text |Cite
|
Sign up to set email alerts
|

Native mass spectrometry reveals the conformational diversity of the UVR8 photoreceptor

Abstract: SignificanceThe plant photoreceptor UVR8 absorbs UV-B light to regulate UV protection and photomorphogenic responses in plants. Here we show that UVR8 adopts multiple conformations to generate the signaling active state. The conformational diversity of UVR8 was revealed using a native mass spectrometry approach, where the photoreceptor was photoactivated in the ion source. Our analyses show that not only disordered but also ostensibly well-folded regions of UVR8 can adopt highly extended conformations that are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 41 publications
1
49
0
Order By: Relevance
“…For both types of photoreceptors, interaction through a linear VP peptide motif and a folded, light‐regulated interaction domain leads to cooperative, high‐affinity binding of the activated photoreceptor to COP1. We propose that in response to UV‐B light, UVR8 dimers monomerize, exposing a new interaction surface that binds to the COP1 WD40 domain and releases the UVR8 C‐terminal VP motif from structural restraints that prevent its interaction with COP1 in the absence of UV‐B (Yin et al , ; Heilmann et al , ; Camacho et al , ; Wu et al , ). Similarly, the VP motif in the CCT domain of cryptochromes may become exposed and available for interaction upon blue‐light activation of the photoreceptor (Müller & Bouly, ; Wang et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…For both types of photoreceptors, interaction through a linear VP peptide motif and a folded, light‐regulated interaction domain leads to cooperative, high‐affinity binding of the activated photoreceptor to COP1. We propose that in response to UV‐B light, UVR8 dimers monomerize, exposing a new interaction surface that binds to the COP1 WD40 domain and releases the UVR8 C‐terminal VP motif from structural restraints that prevent its interaction with COP1 in the absence of UV‐B (Yin et al , ; Heilmann et al , ; Camacho et al , ; Wu et al , ). Similarly, the VP motif in the CCT domain of cryptochromes may become exposed and available for interaction upon blue‐light activation of the photoreceptor (Müller & Bouly, ; Wang et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…It is proposed that photoreception 'activates' the monomer in some way so that it can interact with relevant proteins to initiate a response (Jenkins, 2014). Such activation could, for instance, involve observed conformational changes to the monomer (Heilmann et al, 2014;Miyamori et al, 2015;Zeng et al, 2015;Camacho et al, 2019). There is evidence that conformational changes to the monomer alter the exposure of the C-terminal region that interacts with other proteins (Camacho et al, 2019).…”
Section: Uvr8 Monomer Photoreception Likely Contributes To Uv-b Percementioning
confidence: 99%
“…Such activation could, for instance, involve observed conformational changes to the monomer (Heilmann et al, 2014;Miyamori et al, 2015;Zeng et al, 2015;Camacho et al, 2019). There is evidence that conformational changes to the monomer alter the exposure of the C-terminal region that interacts with other proteins (Camacho et al, 2019). Current models of UVR8 signalling involve the monomer binding to COP1, which results in stabilisation of HY5 protein (Favory et al, 2009;Rizzini et al, 2011;Huang et al, 2013), which in turn can stimulate downstream responses including its own transcription (Binkert et al, 2014).…”
Section: Uvr8 Monomer Photoreception Likely Contributes To Uv-b Percementioning
confidence: 99%
“…Even though the crystal structure of UVR8 has been solved, the exact roles of the UVR8 N‐ and C‐terminal ends are not well understood (Jenkins 2014). Structural analysis revealed that the C‐terminus of UVR8 C adopts both a compact and extended state, which are postulated to be important for the regulation of UVR8 activity (Camacho et al 2019). In this study, we provide evidence that the last 17 amino acids of UVR8 repress UV‐B signaling by preventing the binding of UVR8 to COP1, thereby hindering UV‐B perception.…”
Section: Discussionmentioning
confidence: 99%
“…Recent structural analyses suggest that the C‐terminal tail of UVR8, including both the C27 and C17 domains, adopts diverse conformations, for example, compact and extended states that are believed to be important for the regulation of UVR8 activity (Camacho et al 2019). However, experimental evidence is not available.…”
Section: Introductionmentioning
confidence: 99%